PENGGUNAAN COMPLETE FEED BERBASIS PAKAN LOKAL TERHADAP KARKAS DAN KUALITAS DAGING KAMBING BLIGON - , Achmad Sadeli ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this studies was to determine the effect of complete feed based on local feed toward carcass and Bligon goat meat quality. Eight months old of Bligon goat with initial body weight of 13.10 Â± 0.79 kg were used in this study. The treatment control diet with conventional feed (R0), R1 one week fermented complete feed (R1) and two weeks fermented complete feed (R2). The composition of complete feed was 20% gliricida leaves, 20% corn straw, 3% corn husk, 6% cassava, 3% teak leaves, 12% banana stems, 6% pollard, 3% rice bran, 0.29% of minerals, 1.20% molasses, 0.01% BiofitÂ® and 25.50% water. The data was consisted of slaughter weight, carcass weight, carcass percentage, physical meat quality (color, pH, water holding capacity, cooking loss and tenderness value) and chemical quality of meat (protein, fat and water contents). One way completely randomized design was used to analysis the effect of feed treatment and continued by Duncanâs new Multiple Range Test (DMRT) for significant differences. The results showed that slaughter weight, carcass weight and carcass percentage were not significantly differs amongst treatments. The pH value and tenderness were also not significantly differs. Meta colour of R0 treatment was higher (P<0.05) than those of R1 and R2. Cooking loss for R0 was lower (P< 0.05) than R1 and R2 while the water holding capacity of R0 was higher (P < 0.05) than R2. Water content was not significantly affected by feed treatments. The protein content of R0 was higher (P< 0.05) than R1 and R2 while the fat content of R0 was higher R2. It is concluded that complete feed offered to Bligon goats produce a similar quality of the slaughter weight, carcass weight, carcass percentage, moisture content, pH value and tenderness meat. Two weeks fermented complete feed can produce lower meat fat content.